2016
DOI: 10.1038/modpathol.2016.82
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic correlates of molecular alterations in extrauterine Müllerian carcinomas

Abstract: Extrauterine high-grade serous carcinomas can exhibit various histologic patterns including (1) classic architecture that is papillary, micropapillary and infiltrative and (2) solid, endometrioid, and transitional (ie, SET) patterns. Although the SET pattern has been associated with germline BRCA mutations, potential molecular underpinnings have not been fully investigated. DNA was isolated from 174 carcinomas of the fallopian tube, ovary, or peritoneum. Targeted next-generation sequencing was performed and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Prior to the recognition of SET features in high-grade serous carcinoma, tumors exhibiting these morphological findings were often misdiagnosed as high-grade endometrioid, transitional cell, or undifferentiated carcinomas. In a more recent study, Ritterhouse et al confirmed that tumors with homologous recombination deficiency, including those diagnosed in BRCA1 and BRCA2 mutation carriers, are six times more likely to exhibit non-classical (SET or ambiguous) features of high-grade serous carcinoma (50). Although the aforementioned features are associated with BRCA-mutated tumors, the data to date have not been able to demonstrate differences to accurately distinguish tumors associated with germline mutations versus somatic mutations and BRCA promoter methylation based on morphology alone.…”
Section: Specific Tumor Characteristicsmentioning
confidence: 98%
See 2 more Smart Citations
“…Prior to the recognition of SET features in high-grade serous carcinoma, tumors exhibiting these morphological findings were often misdiagnosed as high-grade endometrioid, transitional cell, or undifferentiated carcinomas. In a more recent study, Ritterhouse et al confirmed that tumors with homologous recombination deficiency, including those diagnosed in BRCA1 and BRCA2 mutation carriers, are six times more likely to exhibit non-classical (SET or ambiguous) features of high-grade serous carcinoma (50). Although the aforementioned features are associated with BRCA-mutated tumors, the data to date have not been able to demonstrate differences to accurately distinguish tumors associated with germline mutations versus somatic mutations and BRCA promoter methylation based on morphology alone.…”
Section: Specific Tumor Characteristicsmentioning
confidence: 98%
“…Prior to the recognition of SET features in high-grade serous carcinoma, tumors exhibiting these morphological findings were often misdiagnosed as high-grade endometrioid, transitional cell, or undifferentiated carcinomas. In a more recent study, Ritterhouse et al confirmed that tumors with homologous recombination deficiency, including those diagnosed in BRCA1 and BRCA2 mutation carriers, are six times more likely to exhibit non-classical (SET or ambiguous) features of high-grade serous carcinoma ( 50 ).…”
Section: Hboc-associated Tubo-ovarian Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Other features more frequently observed in BRCA1-associated HGSOC are necrosis, a higher mitotic index, and an increased number of tumor-infiltrating lymphocytes (TILs; refs. [18][19][20]. On a molecular level, gBRCA-associated breast cancers and OCs share similar somatic copy-number profiles [somatic copy-number alteration (SCNA)-high] and frequent TP53 mutations (16)(17)(18)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…HGSC show a relatively high number of somatic copy number variations and structural variations with >100 recurrent amplifications and deletions identified [13][14][15]. Distinct clinical features and several morphological patterns of HGSC have been described and linked to specific genomic mutations, such as BRCA1/ BRCA2, which confer a better prognosis, but this needs to be validated [16,17].…”
Section: Serous Carcinomasmentioning
confidence: 99%